Analisis Faktor Penghambat Penerapan Sistem Informasi Manajemen Puskesmas di Indonesia: Literature Review - Yuskaini Hadijah Rambe; Salwa Muthi’ah Siregar; Zahra Andini; Sri Hajijah Purba (CV. ITTC INDONESIA, 2024)
There are a number of challenges facing Indonesia's Community Health Center Management Information System (SIMPUS) adoption. The application of SIMPUS is hampered by a number of variables, according to earlier studies. The purpose of this study is to investigate the barriers to SIMPUS implementation, as demonstrated by Indonesian Community Health Centers. This study is a literature review that utilizes secondary data from publications published in the Google Scholar database between 2018 and 2023 and is relevant to the topic of discussion. The results showed that there were 892 articles that matched the search terms, but 871 articles were excluded because they were duplicates, could not be accessed in full paper form, did not match the topic, exceeded the specified year, or were indicated as assignments/thesis/dissertation. This left 24 articles to be tested for eligibility, which resulted in 17 articles that passed the feasibility test and would undergo narrative synthesis. Analysis shows that obstacles to implementing SIMPUS in Indonesia are caused by various factors including technology, infrastructure, human resources, policies and management support, as well as benefits.